The effect of increasing retirement age on households' savings and consumption expenditure - Stefan Etgeton; Björn Fischer; Han Ye (Journal of Public Economics, 2023)
This paper examines how households adjust their savings and consumption expenditure in response to an anticipated increase in the early retirement age (ERA). We examine the 1999 pension reform in Germany, which increased the ERA for women born after 1951 by at least three years. First, we present suggestive evidence that women update their retirement planning in response to the reform. Using the German Income and Consumption Survey, we find a negative impact on private savings of 0.6 percentage points that is driven by households with married women. We show that households consisting of highly educated women and homeowners are more likely to reduce their savings rates. Furthermore, we find that the treated households increase their leisure spending while maintaining an unchanged level of disposable income. Our findings suggest that the households anticipate experiencing a lifetime income increase and reduce their savings rate to smooth consumption.
Keywords: D14; J14; J26; 330; Pension reform; early retirement age; savings; pension wealth; consumption expenditure